2019
DOI: 10.1111/bph.14649
|View full text |Cite
|
Sign up to set email alerts
|

Small molecule‐facilitated anion transporters in cells for a novel therapeutic approach to cystic fibrosis

Abstract: Background and Purpose: Cystic fibrosis (CF) is a lethal autosomal recessive genetic disease that originates from the defective function of the CF transmembrane conductance regulator (CFTR) protein, a cAMP-dependent anion channel involved in fluid transport across epithelium. Because small synthetic transmembrane anion transporters (anionophores) can replace the biological anion transport mechanisms, independent of genetic mutations in the CFTR, such anionophores are candidates as new potential treatments for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 66 publications
2
35
0
1
Order By: Relevance
“…54 Encouragingly, the present results and ref. 41 demonstrate that the action of anionophores is additive to the clinically-licensed CFTR modulators lumacaor and ivacaor, raising the possibility that combination therapy with anionophores and CFTR modulators might be used to treat CF patients. While ivacaor and lumacaor are orally bioavailable drugs, 39,40 we envisage that anionophores would be delivered to the lungs of CF patients by aerosolization as for inhaled antibiotics and gene therapy vectors.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…54 Encouragingly, the present results and ref. 41 demonstrate that the action of anionophores is additive to the clinically-licensed CFTR modulators lumacaor and ivacaor, raising the possibility that combination therapy with anionophores and CFTR modulators might be used to treat CF patients. While ivacaor and lumacaor are orally bioavailable drugs, 39,40 we envisage that anionophores would be delivered to the lungs of CF patients by aerosolization as for inhaled antibiotics and gene therapy vectors.…”
Section: Discussionmentioning
confidence: 98%
“…They also support a variety of potential therapeutic applications for anionophores, some as anticancer and antimicrobial agents, [45][46][47] but others as CF therapeutics. 29,41,48 If anionophores are to be used as research tools, it is important to establish their sensitivity to small molecules that inhibit endogenous anion transport systems. We therefore studied the effects of CaCC inh -A01 (active against CaCC) and CFTR inh -172 (active against CFTR), 36,37 on transport by 11, 12, 15 and 19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anionophore-facilitated halide transport was then expressed as the initial quenching rate of the Yellow Fluorescent Protein (YFP) upon an extracellular application of iodide. We already demonstrated that MM3 facilitates a significant iodide transport in FRT cells, requiring 2.8 ± 0.6 µM to induce half of the maximum transport rate [22]. Instead, the halide transport capacity of MM34 was not previously assayed in mammalian cells.…”
Section: Halide Transport Experiments On Fisher Rat Thyroid Cellsmentioning
confidence: 98%
“…Previous studies have identified several anionophores inspired by natural products such as prodiginines and tambjamines, able to transport halides in mammalian cells at non-toxic concentrations [18][19][20][21]. Transmembrane transport activities comparable to that of the native CFTR were measured for the best tambjamines candidates [22]. Although promising, these results were not obtained in a physiologically relevant disease model.…”
Section: Introductionmentioning
confidence: 99%